Method for in-situ preparation of polyphenylene sulfide-based membrane electrode
Through plasma treatment and laser engraving technology, a polyphenylene sulfide-based film electrode with high hydrophilicity and conductivity was prepared, solving the problem of high energy consumption in the process of alkaline electrolysis of hydrogen production, and achieving more efficient hydroxide ion transmission and current density.
Patent Information
- Application Number
- CN202510144121.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-10
AI Technical Summary
The existing polyphenylene sulfide (PPS) membranes have problems such as poor airtightness, difficulty in transporting hydroxide ions, high membrane resistance and low current density during the process of alkaline electrolysis of hydrogen, resulting in high energy consumption of electrolytic hydrogen production.
Hydrophilic groups are introduced through plasma treatment, locked in an acidic or alkaline solution, and then the PAN or PVP solution doped with rare earth ions or iron element ions is poured on the surface, and graphene doped with rare earth ions or iron element ions is engraved with carbon dioxide laser to form rare earth ions or iron element ions to prepare a polyphenylene sulfide-based film electrode.
The hydrophilic properties of the polyphenylene sulfide separator are significantly improved, the conductivity and electrochemical properties of the electrode are improved, the energy consumption of electrolytic hydrogen production is reduced, and the possibility of electrode falling off is reduced.
Smart Images

Figure CN119592974A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of hydrogen production by electrolysis of water, and in particular to a method for in-situ preparation of a polyphenylene sulfide-based membrane electrode. Background Art
[0002] Although traditional fossil energy can meet the current energy demand, its unsustainability and impact on the environment are worrying. Finding renewable and clean alternative energy has become the focus of current energy research. Hydrogen energy, as a green and pollution-free energy carrier, realizes the efficient conversion of hydrogen energy and electrical energy through water electrolysis technology. At present, water electrolysis hydrogen production technologies include alkaline water electrolysis, proton exchange membrane (PEM) electrolysis, anion exchange membrane (AEM) electrolysis and solid oxide electrolysis cell (SOEC) electrolysis. Among these technologies, alkaline water electrolysis hydrogen production technology is currently the most mature and commercialized electrolysis hydrogen production technology, with the advantages of simple operation and low production cost.
[0003] The diaphragm is one of the key components of the alkaline electrolyzer. It not only separates the positive and negative electrodes of the battery to prevent short circuits, but also avoids the mixing of gas products at the two electrodes, and provides high ionic conductivity so that hydroxide ions can be transferred from the cathode to the anode. The asbestos diaphragm used in the early days has been eliminated due to its carcinogenicity, easy decomposition, electrolyte pollution, high resistance, and high energy consumption. Then, polyphenylene sulfide (PPS) diaphragm was developed as the second-generation diaphragm. The PPS diaphragm has excellent acid, alkali and solvent resistance, and can operate for a long time in a wet state at 200°C. It is an ideal choice for alkaline electrolyzer diaphragms. However, the PPS diaphragm is essentially a hydrophobic diaphragm, which results in poor air tightness of the diaphragm, and there are disadvantages such as difficulty in the transmission of hydroxide ions, high membrane resistance and low current density, which greatly increases the energy consumption of hydrogen production by electrolysis. At the same time, in order to reduce the impedance between the electrode and the membrane, non-precious metal catalyst materials are currently pressed onto the surface of the membrane. Although this technology can greatly reduce the impedance of charge transfer, the electrode will fall off during long-term use, thereby reducing the efficiency of water electrolysis.
[0004] At present, the hydrophilic modification of PPS mainly includes: 1) Oxidation method. The oxidation treatment of polyphenylene sulfide is carried out with strong oxidants such as strong acid or hydrogen peroxide. Although this method can increase the hydrophilicity of polyphenylene sulfide, it also destroys the molecular chain of polyphenylene sulfide itself and introduces hydrophilic groups during the oxidation process, which will reduce the service life of polyphenylene sulfide in high-concentration alkaline solutions. In high-concentration alkaline solutions, hydroxide will attack the carbon atoms on the destroyed molecular chain, leading to the decomposition of polyphenylene sulfide. 2) Grafting some hydrophilic molecular chains on the surface, but most polar molecular chains are not alkali-resistant. Summary of the invention
[0005] In view of the deficiencies in the prior art, the technical problem to be solved by the present invention is to provide a method for in-situ preparation of polyphenylene sulfide-based membrane electrodes.
[0006] The technical solution of the present invention to solve the technical problem is to provide a method for in-situ preparation of a polyphenylene sulfide-based membrane electrode, characterized in that the method comprises the following steps: Step 1, subjecting the polyphenylene sulfide cloth to plasma treatment to make the surface of the polyphenylene sulfide have hydrophilic groups; then immersing the treated polyphenylene sulfide cloth in an acidic solution or an alkaline solution, and then washing and drying to obtain a hydrophilic polyphenylene sulfide membrane; Step 2, pouring a layer of PAN or PVP solution doped with rare earth ions or iron element ions on the surface of the hydrophilic polyphenylene sulfide membrane in step 1, and drying to obtain a composite polyphenylene sulfide membrane; Step 3: Use carbon dioxide laser engraving to laser engrave the PAN or PVP polymer layer containing rare earth ions or iron-based element ions in the composite polyphenylene sulfide membrane of step 2 to form graphene doped with rare earth ions or iron-based element ions, and obtain a polyphenylene sulfide-based membrane electrode for alkaline water electrolysis.
[0007] Compared with the prior art, the present invention has the following beneficial effects: (1) The present invention first uses plasma treatment to introduce oxygen-containing groups such as -OH, -CO-, -COOH and -CHO, or groups such as -NH2, etc. on the surface of PPS, which significantly improves the hydrophilicity of PPS. Then, an acidic solution or an alkaline solution is used to lock the hydrophilic groups introduced by plasma on the surface of polyphenylene sulfide fiber, so that it has good hydrophilicity without oxidation or grafting treatment, thereby improving the defect that the hydrophilic functional groups on the surface of the PPS film after plasma treatment are time-sensitive.
[0008] (2) The temperature requirement of the present invention is relatively loose. Compared with the traditional high-temperature carbonization method, there are fewer factors to consider. The experimental environment is mild, the preparation is simpler, safer and controllable, and only tens of seconds of laser sintering are required to prepare electrode materials with catalytic function. The production cycle is shorter and the energy consumption is low, which solves the problem of high energy consumption caused by the high temperature requirement of the traditional CVD method for synthesis.
[0009] (3) The present invention is simple and feasible, the raw materials used are low in cost, and the laser engraving process is simple. At the same time, the electrode material is generated in situ on the membrane surface, reducing the possibility of electrode detachment during later use. This method is suitable for mass production and has greater application potential in commercial applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1 This is a hydrophilicity test diagram of the hydrophilic polyphenylene sulfide membrane prepared in step 1 of Example 1 of the present invention; Figure 2This is a hydrophilicity test diagram of the polyphenylene sulfide membrane prepared in step 1 of comparative example 1 of the present invention; Figure 3 This is a photo of the composite polyphenylene sulfide membrane prepared in step 2 of Example 1 of the present invention; Figure 4 This is a photo of the polyphenylene sulfide-based membrane electrode prepared in step 3 of Example 1 of the present invention; Figure 5 This is a resistance test diagram of the composite polyphenylene sulfide separator prepared in step 2 of Example 1 of the present invention; Figure 6 This is a resistance test diagram of the polyphenylene sulfide-based membrane electrode prepared in step 3 of Example 1 of the present invention; Figure 7 This is a graph of the electrochemical performance of the polyphenylene sulfide-based membrane electrode prepared in Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0011] The specific embodiments of the present invention are given below. The specific embodiments are only used to further illustrate the present invention in detail and do not limit the protection scope of the claims of the present invention.
[0012] The present invention provides a method for in-situ preparation of a polyphenylene sulfide-based membrane electrode (hereinafter referred to as the method), characterized in that the method comprises the following steps: Step 1, plasma-treating the polyphenylene sulfide cloth to make the polyphenylene sulfide surface have hydrophilic groups; then immersing the treated polyphenylene sulfide cloth in an acidic solution or an alkaline solution, locking the hydrophilic groups on the surface with the acidic solution or the alkaline solution, and then washing and drying to obtain a hydrophilic polyphenylene sulfide membrane having hydrophilic groups on the fiber surface (hereinafter referred to as a hydrophilic polyphenylene sulfide membrane); Preferably, in step 1, the polyphenylene sulfide cloth is commercial polyphenylene sulfide cloth.
[0013] Preferably, in step 1, the plasma treatment time is 100-400 s, the temperature is room temperature, and the frequency is 10-15 MHz.
[0014] Preferably, in step 1, the hydrophilic group is -OH, -CO-, -COOH, -CHO and -NH2.
[0015] Preferably, in step 1, the treated polyphenylene sulfide cloth is quickly placed in an acidic solution or an alkaline solution to minimize the loss of surface hydrophilic groups.
[0016] Preferably, in step 1, the acidic solution is an acidic aqueous solution, and the alkaline solution is an alkaline aqueous solution.
[0017] Preferably, in step 1, the pH of the acidic solution is 1-6, and the pH of the alkaline solution is 8-14.
[0018] Preferably, in step 1, the acid source of the acidic solution is a weak acid, specifically formic acid, acetic acid or phosphoric acid; the alkali source of the alkaline solution is a water-soluble strong base or weak base, specifically sodium hydroxide, potassium hydroxide or ammonia water.
[0019] Preferably, in step 1, the soaking time is 24-48 hours and the soaking temperature is 30-60°C.
[0020] Preferably, in step 1, the cleaning process is: cleaning with deionized water to remove acid and base ions on the surface until the surface of the polyphenylene sulfide membrane is neutral.
[0021] Preferably, in step 1, the drying process is: drying at 40-60° C. for 0.5-5 h (preferably 1-3 h) to remove surface water molecules.
[0022] Step 2, pouring a layer of PAN or PVP solution doped with rare earth ions or iron element ions on the surface of the hydrophilic polyphenylene sulfide membrane in step 1, and drying to obtain a composite polyphenylene sulfide membrane; Preferably, in step 2, the casting process is scraping, coating or film scraping.
[0023] Preferably, in step 2, the pouring temperature is room temperature and the pouring thickness is 50-100 μm.
[0024] Preferably, in step 2, in the PAN or PVP solution doped with rare earth ions or iron-based element ions, the mass fraction of the rare earth ion salt or the iron-based element ion salt is 0.5% to 2wt%, and the mass fraction of PAN or PVP is 10 to 15wt%.
[0025] Preferably, in step 2, the rare earth ion is a cerium ion, the rare earth ion salt is cerium nitrate; the iron element ion is a ferrous ion (Fe 2+ ), divalent cobalt ion (Co 2+ ) and divalent nickel ions (Ni 2+ ), and the iron-based element ion salt is ferrous nitrate, cobalt nitrate and nickel nitrate.
[0026] Preferably, in step 2, the drying process is: drying at 30-70° C. for 2-12 h (preferably 3-6 h) to remove organic solvents and water molecules in the film.
[0027] Step 3: Use carbon dioxide laser engraving to laser engrave the PAN or PVP polymer layer containing rare earth ions or iron-based element ions in the composite polyphenylene sulfide diaphragm of step 2, decompose carbon dioxide into carbon oxygen free radicals, and interact with -CN of PAN or -CO of PVP and rare earth ions or iron-based element ions in the polymer layer. The polymer layer after the action is rapidly carbonized at high temperature to form graphene doped with rare earth ions or iron-based element ions, thereby obtaining a polyphenylene sulfide-based membrane electrode for alkaline water electrolysis (hereinafter referred to as polyphenylene sulfide-based membrane electrode).
[0028] Preferably, in step 3, the process of carbon dioxide laser engraving is: power is 10-20W, and engraving speed is 200-500mm / s.
[0029] Example 1: Step 1, at room temperature, commercial polyphenylene sulfide cloth was plasma treated for 100 seconds at a frequency of 13 MHz; then the treated polyphenylene sulfide cloth was immersed in a formic acid solution with a pH of 1 at 50° C. for 24 hours, then washed with deionized water until neutral, and dried in an oven at 40° C. for 5 hours to obtain a hydrophilic polyphenylene sulfide membrane; Step 2, dissolving cerium nitrate and PAN in DMF to prepare a PAN solution doped with cerium ions, wherein the mass fraction of cerium nitrate is 2wt% and the mass fraction of PAN is 10wt%; then using a coater to coat the surface of the hydrophilic polyphenylene sulfide membrane with the PAN solution doped with cerium ions to a thickness of 50 μm, and drying at 30° C. for 12 hours to obtain a composite polyphenylene sulfide membrane; Step 3: Use a carbon dioxide laser engraving machine to laser engrave the surface of the composite polyphenylene sulfide diaphragm, with an engraving power of 10 W and an engraving speed of 200 mm / s to obtain a polyphenylene sulfide-based membrane electrode.
[0030] After testing, it was found that the water contact angle of the hydrophilic polyphenylene sulfide membrane was significantly reduced, and the wetting time was shortened. The prepared membrane electrode formed an alkaline water electrolysis cell and showed good performance.
[0031] Depend on Figure 1 It can be seen that the hydrophilic polyphenylene sulfide membrane obtained in step 1 of Example 1 was placed for 3 hours and then subjected to a contact angle test, which showed that the contact angle was 85° and the wetting time was 10 seconds.
[0032] Depend on Figure 3 It can be seen that the surface of the hydrophilic polyphenylene sulfide separator is uniformly coated with the PAN solution doped with cerium ions.
[0033] Depend on Figure 4 It can be seen that the surface of the film is carbonized rapidly after laser engraving.
[0034] Depend on Figure 5 It can be seen that the composite polyphenylene sulfide separator of step 2 is not conductive.
[0035] Depend on Figure 6 It can be seen that the polyphenylene sulfide-based membrane electrode of step 3 is conductive and exhibits a small resistance of 42.2Ω.
[0036] Depend on Figure 5 and Figure 6 It can be seen that after the carbon dioxide laser engraving treatment, the non-conductive composite polyphenylene sulfide diaphragm is carbonized, and the obtained polyphenylene sulfide-based membrane electrode is conductive.
[0037] Comparative Example 1: The method is exactly the same as Example 1, except that: in step 1, only plasma treatment is performed, specifically: step 1, at room temperature, commercial polyphenylene sulfide cloth is plasma treated for 100 seconds at a frequency of 13 MHz to obtain a polyphenylene sulfide membrane.
[0038] Depend on Figure 2 It can be seen that the contact angle test was conducted after the polyphenylene sulfide membrane obtained in step 1 of comparative example 1 was placed for 3 hours, and the contact angle was 121°, the surface was super-hydrophobic, and did not wet, so the performance of the prepared membrane electrode composition alkaline water electrolysis cell was poor.
[0039] Depend on Figure 1 and Figure 2 By comparison, it can be seen that after plasma treatment, immersion in acidic or alkaline solution can lock the hydrophilic groups on the surface.
[0040] Depend on Figure 7 It can be seen that the surface resistance of the membrane electrode of Example 1 shows an obvious downward trend with the increase of current density, and the surface resistance of the membrane electrode of Comparative Example 1 decreases less with the increase of current density. Therefore, the alkaline water electrolysis cell composed of the membrane electrode prepared in Example 1 shows better performance.
[0041] Example 2: Step 1, at room temperature, commercial polyphenylene sulfide cloth was plasma treated for 200 seconds at a frequency of 15 MHz; then the treated polyphenylene sulfide cloth was immersed in an acetic acid solution with a pH of 5 at 60° C. for 36 hours, then washed with deionized water until neutral, and dried in an oven at 50° C. for 2 hours to obtain a hydrophilic polyphenylene sulfide membrane; Step 2, dissolving cobalt nitrate and PAN in DMF to prepare a PAN solution doped with cobalt ions, wherein the mass fraction of cobalt nitrate is 0.5wt% and the mass fraction of PAN is 15wt%; then using a coater to coat the surface of the hydrophilic polyphenylene sulfide membrane with the PAN solution doped with cobalt ions to a thickness of 100 μm, and drying at 70° C. for 2 hours to obtain a composite polyphenylene sulfide membrane; Step 3: Use a carbon dioxide laser engraving machine to laser engrave the surface of the composite polyphenylene sulfide diaphragm, with an engraving power of 10 W and an engraving speed of 300 mm / s to obtain a polyphenylene sulfide-based membrane electrode.
[0042] After testing, it was found that the water contact angle of the hydrophilic polyphenylene sulfide membrane was significantly reduced, and the wetting time was shortened. The prepared membrane electrode formed an alkaline water electrolysis cell and showed good performance.
[0043] Example 3: Step 1, at room temperature, commercial polyphenylene sulfide cloth was plasma treated for 200 seconds at a frequency of 10 MHz; then the treated polyphenylene sulfide cloth was immersed in a potassium hydroxide solution with a pH of 10 at 60° C. for 48 hours, then washed with deionized water until neutral, and placed in an oven at 60° C. for 0.5 hours to obtain a hydrophilic polyphenylene sulfide membrane; Step 2, dissolving nickel nitrate and PAN in DMF to prepare a PAN solution doped with nickel ions, wherein the mass fraction of nickel nitrate is 0.5wt% and the mass fraction of PAN is 15wt%; then using a coater to coat the surface of the hydrophilic polyphenylene sulfide membrane with a thickness of 100μm of the PAN solution doped with nickel ions, and drying at 50°C for 12h to obtain a composite polyphenylene sulfide membrane; Step 3: Use a carbon dioxide laser engraving machine to laser engrave the surface of the composite polyphenylene sulfide diaphragm at an engraving power of 20 W and an engraving speed of 200 mm / s to obtain a polyphenylene sulfide-based membrane electrode.
[0044] After testing, it was found that the water contact angle of the hydrophilic polyphenylene sulfide membrane was significantly reduced, and the wetting time was shortened. The prepared membrane electrode formed an alkaline water electrolysis cell and showed good performance.
[0045] Example 4: Step 1, at room temperature, commercial polyphenylene sulfide cloth was plasma treated for 200 seconds at a frequency of 12 MHz; then the treated polyphenylene sulfide cloth was immersed in a sodium hydroxide solution with a pH of 14 at 30°C for 48 hours, then washed with deionized water until neutral, and dried in an oven at 50°C for 3 hours to obtain a hydrophilic polyphenylene sulfide membrane; Step 2, dissolving ferrous nitrate and PAN in DMF to prepare a PAN solution doped with iron ions, wherein the mass fraction of ferrous nitrate is 2wt% and the mass fraction of PAN is 15wt%; then using a coater to coat the surface of the hydrophilic polyphenylene sulfide membrane with the PAN solution doped with iron ions to a thickness of 100 μm, and drying at 30° C. for 6 hours to obtain a composite polyphenylene sulfide membrane; Step 3: Use a carbon dioxide laser engraving machine to laser engrave the surface of the composite polyphenylene sulfide diaphragm, with an engraving power of 10 W and an engraving speed of 500 mm / s to obtain a polyphenylene sulfide-based membrane electrode.
[0046] After testing, it was found that the water contact angle of the hydrophilic polyphenylene sulfide membrane was significantly reduced, and the wetting time was shortened. The prepared membrane electrode formed an alkaline water electrolysis cell and showed good performance.
[0047] Any matters not described in the present invention are applicable to the prior art.
Claims
1. A method for in-situ preparation of a polyphenylene sulfide-based membrane electrode, characterized in that: The method comprises the following steps: Step 1, subjecting the polyphenylene sulfide cloth to plasma treatment to make the surface of the polyphenylene sulfide have hydrophilic groups; then immersing the treated polyphenylene sulfide cloth in an acidic solution or an alkaline solution, and then washing and drying to obtain a hydrophilic polyphenylene sulfide membrane; Step 2, pouring a layer of PAN or PVP solution doped with rare earth ions or iron element ions on the surface of the hydrophilic polyphenylene sulfide membrane in step 1, and drying to obtain a composite polyphenylene sulfide membrane; Step 3: Use carbon dioxide laser engraving to laser engrave the PAN or PVP polymer layer containing rare earth ions or iron-based element ions in the composite polyphenylene sulfide membrane of step 2 to form graphene doped with rare earth ions or iron-based element ions, and obtain a polyphenylene sulfide-based membrane electrode for alkaline water electrolysis.
2. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 1, characterized in that: In step 1, the plasma treatment time is 100-400 s, the temperature is room temperature, and the frequency is 10-15 MHz.
3. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 1, characterized in that: In step 1, the treated polyphenylene sulfide cloth is quickly placed in an acidic solution or an alkaline solution to reduce the loss of surface hydrophilic groups.
4. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 1, characterized in that: In step 1, the pH of the acidic solution is 1-6, and the pH of the alkaline solution is 8-14; In step 1, the acid source of the acidic solution is a weak acid; the alkali source of the alkaline solution is a water-soluble strong base or weak base; In step 1, the soaking time is 24-48 hours and the soaking temperature is 30-60°C; In step 1, the cleaning process is: cleaning with deionized water to remove acid and alkali ions on the surface until the surface of the polyphenylene sulfide diaphragm is neutral; In step 1, the drying process is: drying at 40-60°C for 0.5-5h.
5. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 4, characterized in that: The acid source of the acidic solution is formic acid, acetic acid or phosphoric acid; the alkali source of the alkaline solution is sodium hydroxide, potassium hydroxide or ammonia water.
6. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 1, characterized in that: In step 2, the casting process is scraping, coating or scraping film; In step 2, the pouring temperature is room temperature and the pouring thickness is 50-100 μm.
7. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 1, characterized in that: In step 2, in the PAN or PVP solution doped with rare earth ions or iron-based element ions, the mass fraction of the rare earth ion salt or the iron-based element ion salt is 0.5% to 2wt%, and the mass fraction of the PAN or PVP is 10 to 15wt%.
8. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 1, characterized in that: In step 2, the rare earth ion is a cerium ion, and the rare earth ion salt is cerium nitrate; the iron-based element ion is at least one of a ferrous ion, a divalent cobalt ion and a divalent nickel ion, and the iron-based element ion salt is ferrous nitrate, cobalt nitrate and nickel nitrate.
9. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 1, characterized in that: In step 2, the drying process is: drying at 30-70°C for 2-12 hours.
10. The method for in-situ preparation of polyphenylene sulfide-based membrane electrode according to claim 1, characterized in that: In step 3, the process of CO2 laser engraving is: power is 10~20W, engraving speed is 200~500mm / s.
Citation Information
Patent Citations
Preparation method of polyphenylene sulfide ceramic composite membrane for lithium ion battery
CN105280863A
Laser induced graphene materials and their use in electronic devices
CN106232520A
Preparation method of novel microporous diaphragm for alkaline electrolyzed water, obtained product and application
CN116024825A
Flexible electro-catalytic hydrogen evolution electrode material generated from laser direct writing polyimide composite material, preparation method and flexible hydrogen evolution electrode prepared from flexible electro-catalytic hydrogen evolution electrode material
CN116180131A
Preparation method of alkaline water electrolysis composite diaphragm and alkaline water electrolysis composite diaphragm
CN117403276A
Cited By
Preparation method of nano Mg (OH) 2-PPS fabric composite diaphragm
CN121407150A